2022
DOI: 10.3390/ijerph19095249
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Project-Based Learning Program on High-Risk Newborn Care for Nursing Students and Its Effects: A Quasi-Experimental Study

Abstract: Project-based learning (PjBL) allows nursing students to participate in real problem-solving, construct knowledge, and improve their nursing skills in the process of accomplishing meaningful projects. This study was conducted to develop a PjBL program on high-risk newborn care for nursing students and evaluate its effects. A quasi-experimental study using a nonequivalent control group pretest–posttest design was employed between June and December 2021. The participants were 45 nursing students (24 in the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Moreover, it can enhance cooperative skills among students [ 31 ], and effective communication, which is a critical skill for nurses [ 37 , 38 ]. Previous studies that applied collaborative learning to nursing students’ clinical practicum confirmed its effectiveness in enhancing nursing competencies [ 39 , 40 ]. Therefore, nurse educators who instruct courses on global health should consider applying a collaborative learning approach to improve communication skills among nursing students.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, it can enhance cooperative skills among students [ 31 ], and effective communication, which is a critical skill for nurses [ 37 , 38 ]. Previous studies that applied collaborative learning to nursing students’ clinical practicum confirmed its effectiveness in enhancing nursing competencies [ 39 , 40 ]. Therefore, nurse educators who instruct courses on global health should consider applying a collaborative learning approach to improve communication skills among nursing students.…”
Section: Discussionmentioning
confidence: 93%
“…Cabe ainda salientar que a ABPj é capaz de proporcionar oportunidade aos estudantes de vivenciar a construção de um projeto, em vários cursos da área de saúde, a experiência e o contato com o planejamento e o desenvolvimento de um projeto possibilita a aquisição de habilidades e de competências importantes para o trabalho na área de saúde. Como observado, um estudo que utilizou a ABPj para desenvolver um programa sobre cuidados com recém-nascidos de alto risco para estudantes de enfermagem e examinar seus efeitos, envolveu a produção de um videoclipe educativo sobre cuidados com recém-nascidos de alto risco para estudantes de enfermagem, revelando que o programa foi eficaz para melhorar a competência dos estudantes em enfermagem para recém-nascidos de alto risco e diminuir o estresse relacionado ao estágio (Koo;Gu;Lee, 2022). A aplicação do ABPj ao ensino da prática clínica contribui para a melhoria das competências de enfermagem, incentivando os estudantes a se envolverem na aprendizagem ativa e, ao mesmo tempo, produzirem resultados significativos, portanto, a aplicação do ABPj pode ser considerada em vários locais de prática clínica (Koo;Gu;Lee, 2022).…”
Section: Discussionunclassified
“…Proposing a change in methodology, encouraging active learning [5], and offering the freedom to interpret the required content can generate some difficulty and restlessness in those who are used to greater precision. In addition, that which, in principle, we consider as an opportunity to expand the possibilities of intervention is considered a burden that generates insecurity and requires greater involvement of both teachers and students.…”
Section: Discussionmentioning
confidence: 99%
“…Research in nursing students through project-based learning is being used through different methodological designs. We found studies with a quasi-experimental study design using a pretest-posttest design of a non-equivalent control group [5] or accounts of experiences on the use of PBL in the course of educational actions in nursing practice [6]. PBL is also being used in professional-level training for quality-of-care improvement by using project-based learning to teach advanced practice nurses [7].…”
Section: Introductionmentioning
confidence: 99%